Prevalence of polymorphisms in OPG, RANKL and RANK as potential markers for Charcot arthropathy development - Bożena Bruhn-Olszewska (Nature Portfolio, 2017)
Abstract Charcot arthropathy is one of the most serious complications of diabetic foot syndrome that leads to amputation of the affected limb. Since there is no cure for Charcot arthropathy, early diagnosis and implementation preventive care are the best available treatment. However, diagnosis is hindered by obscure clinical picture of the disease and lack of molecular markers for its early detection. Results of recent research suggest that OPG-RANKL-RANK axis regulating bone metabolism can be associated with Charcot arthropathy and that SNPs in OPG gene are associated with the disease. Here we report the results of comprehensive analysis of ten SNPs in OPG, RANKL and RANK genes in 260 subjects divided into diabetes, neuropathy and Charcot arthropathy groups. Besides genotype analysis we performed linkage disequilibrium and hierarchical clustering to obtain information about correlation between SNPs. Our results show that OPG 245T/G (rs3134069) and OPG 1217C/T (rs3102734) polymorphisms co-occur in patients with Charcot arthropathy (r2 = 0.99). Moreover, hierarchical clustering revealed a characteristic profile of all SNPs in Charcot arthropathy and neuropathy, which is distinct from control group. Our results suggest that analysis of multiple SNPs can be used as potential marker of Charcot arthropathy and provide insight into possible molecular mechanisms of its development.